Penyuluhan Pentingnya Gizi Seimbang Saat Pandemi Covid 19 pada Remaja Karang Taruna - Nechita Dinda Febytia; Inne Indraaryani Suryaalamsyah (Sarana Ilmu Indonesia (salnesia), 2022)
Corona viruses are a subfamily of viruses that are caused by disease in humans and animals. In humans it causes respiratory tract infections, ranging from the common cold to serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). This community service aims to increase knowledge about the importance of a balanced nutritious diet. The method of implementing counseling boldly to youth youth in RW 15, Mekarjaya Village, Sukmajaya District, Depok City, using lecture, discussion and question and answer methods related to the importance of balanced nutrition during a pandemic. The results obtained were an increase in the knowledge of youth youth groups regarding the importance of balanced nutrition during a pandemic.